2017
DOI: 10.15406/jpnc.2017.07.00281
|View full text |Cite
|
Sign up to set email alerts
|

" The Laparoscopic Assisted Duhamel Pull through Procedure for Hirschsprung’s Disease: Our Technique and Short Term Results "

Abstract: Aims: To prospectively evaluate the laparoscopic assisted Duhamel pull through (LADPT) procedure for Hirschsprung's disease at our centre. Material and methods:After clinico-radiological diagnosis of Hirschsprung's disease junctional colostomy and mutltiple seromuscular biopsy was taken. After histological confirmation of diagnosis definitive surgery was done by laparoscopic assisted Duhamal procedure. Mobilization of aganglionic bawel and colon proximal to leveling colostomy was done laproscopically. The leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In present study, group I patients underwent Modified Duhamel's procedure and group II patients underwent transanal endorectal pull-through procedure. Singh et al [8] found that mean age of surgery was 6.0±0.23 months comparable in both groups (ranged 3 m-5 yrs). Mean operative time, blood loss and hospital stay with range were 80±0.30 (70-100 minutes), 50±0.20 (40-90 ml) and 6±0.21 (3-12 days) less in LADPT cases compared with open Duhamel (p value .008, 0.0067 and .009 respectively).…”
Section: Discussionmentioning
confidence: 84%
“…In present study, group I patients underwent Modified Duhamel's procedure and group II patients underwent transanal endorectal pull-through procedure. Singh et al [8] found that mean age of surgery was 6.0±0.23 months comparable in both groups (ranged 3 m-5 yrs). Mean operative time, blood loss and hospital stay with range were 80±0.30 (70-100 minutes), 50±0.20 (40-90 ml) and 6±0.21 (3-12 days) less in LADPT cases compared with open Duhamel (p value .008, 0.0067 and .009 respectively).…”
Section: Discussionmentioning
confidence: 84%
“…After making a diagnosis through history taking, physical examination and supporting examinations, patients with Hirschprung's disease must be given immediate treatment [9,10,11]. The principle of action in Hirschprung's disease is to resect the aganglionic intestine and pull the ganglionic intestine through a point just above the dentate line [12][13][14]15,16,17].…”
Section: Introductionmentioning
confidence: 99%